Mid-upper-arm and calf circumferences are useful predictors of underweight in women of reproductive age in northern Vietnam - Nguyen, Phuong Hong; Ramakrishnan, Usha; Katz, Benjamin; Gonzalez-Casanova, Ines; Lowe, Alyssa E.; Nguyen, Hieu; Pham, Hoa; Truong, Truong; Nguyen, Son; Martorell, Reynaldo (SAGE Publications, 2014)
Mid-upper-arm circumference (MUAC) and calf circumference (CC) are correlated with body mass index (BMI) in adults and may be useful for screening women with underweight (BMI < 18.5 kg/m2). However, there is no consensus on appropriate MUAC and CC cutoff points in diverse populations, especially in women of reproductive age.To assess the accuracy of different MUAC and CC cutoff points to screen for underweight and to identify the most appropriate cutoff points in a sample of women of reproductive age from rural northern Vietnam.Anthropometric measurements (weight, height, MUAC, CC, and triceps and subscapular skinfold thicknesses) were obtained for 4,981 women of reproductive age who participated in a micronutrient intervention trial (PRECONCEPT) in Thái Nguyên Province, Viet- nam. Receiver operating characteristic (ROC) analysis was used to evaluate different cutoff values of MUAC and CC and identify the most appropriate cutoff values to predict underweight.The overall prevalence of underweight was 32%. The MUAC value of 23.5 cm and the CC value of 31 cm were identified as the best cutoffs based on low misclassification (16% for MUAC and 21% for CC) and good balance of sensitivity (89% and 85%, respectively) and specificity (71% and 67%, respectively. The ROC curves were similar across different ethnic groups, with the area under the curve (AUC) values reaching 0.89 to 0.93 for MUAC and 0.83 to 0.89 for CC.MUAC and CC perform adequately in screening for underweight in women. The utility of these measurements in predicting functional outcomes should be examined.